2016
DOI: 10.15740/has/arjci/7.1/46-51
|View full text |Cite
|
Sign up to set email alerts
|

Influence of micronutrients and growth regulators on the performance of cabbage quality

Abstract: in order to evaluate the performance of micronutrients (Zn and Fe) and growth regulators (Gibberellic acid and Naphthalene acetic acid) alone and their combinations applied as foliar spray for cabbage quality. The different levels of micronutrients were found significant on ascorbic acid and chlorophyll contents of cabbage head, maximum ascorbic acid (49.4 mg/100g fresh wt.) and chlorophyll content (0.412 mg/g fresh wt.) of cabbage head were recorded with treatment M 1 (zinc sulphate 0.5%). Among different lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 4 publications
1
3
0
Order By: Relevance
“…This increase in vitamin C content might be due to application of zinc and iron, both working as active carrier to enzymatic activities and enzymes catalyzing numerous biochemical reactions, including those neutralizing the effects of reactive oxygen species and various pathways of ascorbate synthesis in plants and resulted in to higher vitamin C content in cabbage head. Similar findings of increased vitamin C contents were reported by Kotecha et al (2016) [10] in cabbage and Singh et al (2018) [22] in broccoli.…”
Section: Tss (˚Brix)supporting
confidence: 90%
“…This increase in vitamin C content might be due to application of zinc and iron, both working as active carrier to enzymatic activities and enzymes catalyzing numerous biochemical reactions, including those neutralizing the effects of reactive oxygen species and various pathways of ascorbate synthesis in plants and resulted in to higher vitamin C content in cabbage head. Similar findings of increased vitamin C contents were reported by Kotecha et al (2016) [10] in cabbage and Singh et al (2018) [22] in broccoli.…”
Section: Tss (˚Brix)supporting
confidence: 90%
“…The obtained results were found to be inconsistent with the findings of Kumar et al [38], Mishra et al [39] in knol-khol, Yadav et al [40], Sharma and Kumar [41] in cauliflower, Roni et al [42] in broccoli, Zaki et al [31] in broccoli, and Kotecha et al [43] in cabbage. The increased ascorbic acid content appeared might be due to the application of micronutrients particularly boron which helps in carbohydrate metabolism.…”
Section: Ascorbic Acid Content In Curd (Mg/100g)mentioning
confidence: 60%
“…It was also reported that GA3 increasing plasticity of the cell wall followed by hydrolysis of starch to sugars which lowers the water potential of cell, resulting in the entry of water into cell causing elongation. These results are in accordance with other researchers viz., [7,8] in cauliflower; [9,10,11] in cabbage in cluster bean and [12] in Indian bean.…”
Section: Resultsmentioning
confidence: 99%